The Role of MSMEs in Driving the Regional Economy: A Case Study of Medan City - Richna Handriyani; Shintami Oktavia; Evi Syuriani Harahap (Outline Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have become the main driving force of the local economy in Indonesia, including in Medan City. As grassroots economic entities, MSMEs not only contribute significantly to the Gross Regional Domestic Product (GRDP), but also play a role in creating jobs, reducing social disparities, and accelerating the process of equitable development. This study is a literature review that aims to examine in depth the role of MSMEs in driving the regional economy in Medan City based on the results of the latest research published in national and international journals. The analysis was conducted on various aspects, such as the economic contribution of MSMEs, structural and policy challenges, the role of digitalization in increasing competitiveness, and the social impact on community welfare. The results of the study indicate that MSMEs in Medan City play a central role in economic development, but still face various obstacles such as access to financing, limited digitalization, and managerial limitations. Therefore, a strengthening strategy based on collaboration between MSME actors, local governments, financial institutions, and local communities is needed. This study provides a conceptual contribution in building a comprehensive understanding of the contribution of MSMEs as an instrument of sustainable regional development.